Preparation and Protein Adsorption Properties of HEMA Modified PDMSPES Composite Membranes for ECMO Oxygenation Applications - Siegenfeld, Antonio; Maclay, Yaneer (Journal of Functional Materials and Applied Engineering, 2022)
The clinical efficacy of extracorporeal membrane oxygenation (ECMO) remains severely limited by thrombogenesis and inflammatory responses induced by insufficient hemocompatibility of commercial oxygenation membranes. Herein, we report a facile surface engineering strategy to construct a hydrophilic HEMA-PDMS/PES composite membrane with balanced gas transport performance and antifouling properties. An amphiphilic HEMA-PDMS copolymer was first synthesized via free radical copolymerization, where the grafting density of hydroxyethyl methacrylate (HEMA) was precisely controlled to avoid compromising the intrinsic gas permeability of polydimethylsiloxane (PDMS). The copolymer was then coated on a porous polyethersulfone (PES) substrate fabricated by phase inversion, forming a dense, defect-free functional layer. Systematic characterization confirmed that the composite membrane maintained excellent thermal stability (no mass loss below 400 °C) and achieved a moderate surface water contact angle of ~40°, endowing it with both CO2/O2selectivity (α=6.53) and ultralow hemolysis rate (0.207%–0.434%). Protein adsorption assays demonstrated that HEMA modification reduced the maximum bovine serum albumin (BSA) adsorption capacity by up to 13.494% compared to unmodified PDMS/PES membranes. Combined Langmuir isotherm and pseudo-second-order kinetic fitting revealed that adsorption was dominated by chemisorption via hydrogen bonding between BSA polar residues and HEMA hydroxyl groups, while competitive hydration and hydrophobic interactions jointly modulated the adsorption behavior. This work not only clarifies the protein adsorption mechanism on amphiphilic silicone-based surfaces, but also provides a scalable material design paradigm for next-generation ECMO devices with extended safe operation duration.